2022
DOI: 10.1007/s10763-022-10338-7
|View full text |Cite
|
Sign up to set email alerts
|

Incorrect Ways of Thinking About the Size of Fractions

Abstract: The literature has amply shown that primary and secondary school students have difficulties in understanding rational number size. Many of these difficulties are explained by the natural number bias or the use of other incorrect reasoning such as gap thinking. However, in many studies, these types of reasoning have been inferred from comparing students’ accuracies in multiple-choice items. Evidence that supports that these incorrect ways of reasoning are indeed underlying is scarce. In the present work, we car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
7
0
4
Order By: Relevance
“…In the present study, we chose to control for magnitude difference between the fraction pairs and partial distance. Although, we were not able to exactly match between the conditions on factors like gap distance, half benchmarking, simplified forms, and familiarity, which have been shown to impact performance (Clarke & Roche, 2009; González-Forte et al, 2018, 2020), there does not seem to be a definitive impact of these factors on students’ performance in the current sample (). For example, applying the gap strategy (selecting the fraction with the smallest distance between numerator and denominator) would only lead to an error on one congruent pair (2/7 vs. 3/9), yet performance was no worse on this pair (see ).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the present study, we chose to control for magnitude difference between the fraction pairs and partial distance. Although, we were not able to exactly match between the conditions on factors like gap distance, half benchmarking, simplified forms, and familiarity, which have been shown to impact performance (Clarke & Roche, 2009; González-Forte et al, 2018, 2020), there does not seem to be a definitive impact of these factors on students’ performance in the current sample (). For example, applying the gap strategy (selecting the fraction with the smallest distance between numerator and denominator) would only lead to an error on one congruent pair (2/7 vs. 3/9), yet performance was no worse on this pair (see ).…”
Section: Discussionmentioning
confidence: 66%
“…Contrary to our expectations, participants were more accurate on the incongruent distinct component problems than on the congruent problems. However, a number of previous studies have documented stronger performance for incongruent relative to congruent problems with distinct components (Gómez & Dartnell, 2019; González-Forte et al, 2018, 2020; Obersteiner et al, 2013; Rinne et al, 2017; Viol Ferreira Toledo et al, 2023), which may reflect the strategy that participants engaged in when solving these problems. In these cases, participants (or at least a subset of participants), may have used a “select the smaller number strategy,” which would lead to the correct answer for incongruent but not congruent problems.…”
Section: Discussionmentioning
confidence: 92%
“…Merenluoto and Lehtinen (2004) stated that even students in upper secondary school can be unaware of their misconception and show overconfidence in their natural number-based answers. Similarly, González-Forte et al (2023) showed that seventh-grade students with a clear NNB profile had high confidence levels, when answering a fraction task incorrectly with a natural number-based answer. Moreover, these students were reluctant to adapt their reasoning, when confronted with a student's answer who had reasoned correctly.…”
Section: Natural Number Biasmentioning
confidence: 95%
“…It aims to extend the findings by Halme et al (2022) by assessing whether fraction state anxiety responses differ between low‐performing students with qualitatively different fraction understanding. Previous studies have shown that students with a strong NNB are unaware of their incorrect reasoning and show overconfidence in their incorrect answers (González‐Forte et al, 2023; Merenluoto & Lehtinen, 2004). Therefore, students with a clear NNB may also have low fraction state anxiety despite their poor fraction understanding.…”
Section: Introductionmentioning
confidence: 99%
“…En particular, el documento teórico está formado por información procedente de investigaciones sobre la comprensión de los números racionales en estudiantes de secundaria (González-Forte et al, 2020;González-Forte et al, 2022). Esta información integra diferentes formas de razonar (correctas e incorrectas) de los estudiantes en i) actividades de comparar y ordenar fracciones y números decimales, ii) actividades de suma, resta, multiplicación y división con fracciones y números decimales, y iii) actividades sobre el concepto de densidad.…”
Section: Un Ejemplo De Entorno De Aprendizajeunclassified